2022
DOI: 10.1155/2022/3366343
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Exploration and Analysis of Educational History from the Perspective of Educational Environmental History and Environmental History

Abstract: The emergence of environmental historiography, for the first time, organically combined the history of the environment and human history and began to pay attention to the close relationship between human social changes and environmental changes. This paper explores the impact of environmental history on education from the perspective of environmental history. This paper explores and analyzes the history of the educational environment from the perspective of environmental history and studies the laws and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Miao analyzed the teaching effect of the informatization teaching mode and proposed and constructed the informatization teaching mode based on the network course [2]. Xu introduced the concept, characteristics, and teaching process of the information-based teaching mode and analyzed the teaching consequences [3][4][5][6][7]. e abovementioned research studies described the relevant content of the educational informatization teaching pattern, and the influence of the informatization teaching pattern on education is far-reaching.…”
Section: Introductionmentioning
confidence: 99%
“…Miao analyzed the teaching effect of the informatization teaching mode and proposed and constructed the informatization teaching mode based on the network course [2]. Xu introduced the concept, characteristics, and teaching process of the information-based teaching mode and analyzed the teaching consequences [3][4][5][6][7]. e abovementioned research studies described the relevant content of the educational informatization teaching pattern, and the influence of the informatization teaching pattern on education is far-reaching.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%